2020
DOI: 10.9734/ajess/2020/v10i130258
|View full text |Cite
|
Sign up to set email alerts
|

Employability Skills Needed in Hospitality Industry: A Scopious Review

Abstract: Aim: The purposes of the study were to explain the concept of employability, define employability skills in the context of the hospitality industry, Identify the various employability skills needed in the hospitality industry and to examine the most important employability skills needed by the recruiters’ from various studies conducted in the field of the hospitality industry. Methodology: In this study, only such studies were incorporated which were conducted in the field of the hospitality industry acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…It was shown that QS performs better at generic skills than the technical skills, technical skills were rated fourth and fifth respectively. In this study, Quantity surveyors performed well in communication skills which is in line with Dean and East (2019); Dhaliwal and Misra (2020) who stated the effective communication among workers affect business outcomes positively. This study was against Radermacher et.…”
Section: Figure1 Profession Of the Respondentssupporting
confidence: 79%
“…It was shown that QS performs better at generic skills than the technical skills, technical skills were rated fourth and fifth respectively. In this study, Quantity surveyors performed well in communication skills which is in line with Dean and East (2019); Dhaliwal and Misra (2020) who stated the effective communication among workers affect business outcomes positively. This study was against Radermacher et.…”
Section: Figure1 Profession Of the Respondentssupporting
confidence: 79%
“…Through examining the literature review, it is found that technological advancements in the fourth Industrial revolution changes job requirements in the hospitality industry and also there is need to up-skilling and re-skilling the skills of hospitality professional. Many of the studies reported that in 21 st century leadership skills and communication skills were the most important skills further problem solving, interpersonal , personality development, team work, positive attitude are also commonly needed skills for hospitality professionals [32]. Few studies reported that intervention of technological advancement change the perspective of current hospitality industry.…”
Section: Discussionmentioning
confidence: 99%
“…Organizations are continuously recruiting graduates in order to raise their human capital and enable growth and constant innovation and developments in performance (McDermott, Mangan, & O'Connor, 2006). Findings of the study by Dhaliwal & Misra (2020) highlighted those graduates are expected to possess communication skills of speaking and writing, ethical awareness, conflict management, interpersonal skills, self-development, an ability to work well with a team, an attitude that is positive, self-management, customer orientation skills, management of time, computer sciences and an attitude that is professional.…”
Section: Employers Views On Employability Skills That Graduates Lackmentioning
confidence: 98%